Two new species of Grylloblatta Walker, 1914 (Grylloblattodea: Grylloblattidae) from western North America, and a neotype designation for G. rothi Gurney 1953 - Marshall, Christopher J.; Lytle, David A. (Zootaxa, 2015)
Grylloblatta rothi Gurney, 1953 is redescribed and a neotype is designated from Cultus Mountain in the Oregon Cascades, U.S.A. Two new species of Grylloblatta are described, bringing the total number of Grylloblatta species to 15. Grylloblatta chintimini new species is described from Marys Peak in the Coast Range of Western Oregon, where it occurs on snowpack near the 1250 m summit. Grylloblatta newberryensis new species is described from Newberry Volcano in Central Oregon, where it is associated with snowfields overlying geologically-young lava flows. Morphological characters, primarily derived from male genitalia, are presented to diagnose these species and differentiate them from other Grylloblatta spp. in Oregon, Washington, and California. Molecular sequences from the cytochrome oxidase subunit II gene suggest that significant divergence has occurred among these species and provide a tool to aid identification of juvenile and female specimens.